2018
DOI: 10.1111/cbdd.13188
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of isonicotinic acid hydrazide derivatives with antitubercular activity: Machine learning, molecular docking, synthesis and biological testing

Abstract: The problem of designing new antitubercular drugs against multiple drug-resistant tuberculosis (MDR-TB) was addressed using advanced machine learning methods. As there are only few published measurements against MDR-TB, we collected a large literature data set and developed models against the non-resistant H37Rv strain. The predictive accuracy of these models had a coefficient of determination q = .7-.8 (regression models) and balanced accuracies of about 80% (classification models) with cross-validation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…1,3-Thiazoles 8, 9 containing the 4-chlorophenylsulfonyl group at position C 5 and a substituted amino group at position C 4 are somewhat more active than compound 4 with the morpholino group at position C 5 . Thus, 1,3-thiazole Advanced in vitro study of compounds 5, 19, 21 at five concentrations of the 10-fold dilution (10 -4 -10 -8 М) was also performed towards 60 human cancer cell lines, the set of which was identical to that for the pre-screening stage (Table 2).…”
Section: Biological Evaluationmentioning
confidence: 98%
See 2 more Smart Citations
“…1,3-Thiazoles 8, 9 containing the 4-chlorophenylsulfonyl group at position C 5 and a substituted amino group at position C 4 are somewhat more active than compound 4 with the morpholino group at position C 5 . Thus, 1,3-thiazole Advanced in vitro study of compounds 5, 19, 21 at five concentrations of the 10-fold dilution (10 -4 -10 -8 М) was also performed towards 60 human cancer cell lines, the set of which was identical to that for the pre-screening stage (Table 2).…”
Section: Biological Evaluationmentioning
confidence: 98%
“…It has been demonstrated that 1,3-thiazoles are widely used for creation of dyes, insecticides, herbicides, and pharmaceuticals. Di-and trisubstituted 1,3-thiazole are effective anti-inflammatory, anthelmintic, antiviral, and bactericidal agents [1][2][3][4][5][6]. The nature of the chemical groups in the heterocycle can significantly affect their pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional ML methods, AsNN, RF, kNN, and XGBoost, were also used to generate models predicting antitubercular activities using a training set of 6,337 compounds (Kovalishyn et al, 2018). These molecules were derivatives of azoles, isoniazids, indoles, and others that exhibited MIC values from 1.5 nM to 100 μM.…”
Section: Tuberculosismentioning
confidence: 99%
“…In 2018, novel isonicotinic acid hydrazide derivatives as antitubercular agents determined by ML methods were synthesized by Kovalishyn and coauthors [25]. In this research, 6337 compounds from the various publications which have MIC values ranged from 0.0015 μM to 99.9 μM were selected as initial data set 1.…”
Section: Supervised Learningmentioning
confidence: 99%